Comparison of body pressure distribution in healthy subjects between bubble wrap and an emergency mattress laid on a cardboard bed: a randomized controlled crossover trial - Hamanishi,Seiji; Asada,Yukiko; Ikushima,Yu; Ikeda,Yurika; Chinushi,Mai (PeerJ, 2023)
Background It has been pointed out that the poor environment of evacuation shelters causes health problems and disaster-related deaths among evacuees, and we are concerned that their environment will deteriorate, particularly during a large-scale disaster due to a shortage of daily necessities. In Japan, evacuees usually slept on floors with futons until the Great East Japan Earthquake, but cardboard beds were installed in evacuation shelters. Previous studies have suggested that cardboard beds can reduce cold air transmission from the floor. We have reported that a cardboard bed can have a low-contact pressure dispersion capacity and cannot reduce musculoskeletal strain, unlike a futon or mattress. In the Great East Japan Earthquake, 33% of disaster-related deaths were reported to have been caused by physical or mental fatigue due to living in evacuation shelters. When a large-scale disaster such as the Nankai Trough Earthquake generates huge numbers of evacuees, the supply of mattresses for evacuees will be very difficult. Therefore, we considered potential alternatives that could be produced in large quantities over a short period. Bubble wrap, with very lightweight and waterproofing, could be a good candidate for mattress replacement. This study aimed to investigate the improvement in body pressure distribution and pressure-sensing area when using bubble wrap. Methods Twenty-seven healthy subjects allocated to sequences A and B with different intervention order were laid in supine and lateral positions on a cardboard bed without a mattress, bubble wrap, or air mattress: the mattress-body contact pressure and contour areas were measured, and subjective firmness and comfort during these conditions were also investigated using the visual analog scale (VAS). Acquired data were analyzed using a linear mixed-effects model and Bonferroni’s post-hoc test, and P < 0.05 was considered statistically significant. Results The mattress-body contact pressure and contour area showed significant differences with and without air mattresses. With the air mattresses, the pressure in the supine position decreased by 34%, and that in the lateral position decreased by 13%. However, the four-fold bubble wrap did not improve the mattress-body contact pressure and contour area; the change ratios were within 5% compared to the cardboard bed. However, there were significant differences in subjective firmness and comfort using the VAS among all experimental positions. Conclusion Our study showed that bubble wrap could not significantly improve body pressure concentration and may not be a satisfactory substitute for air mattresses. Because of the improvement in subjective firmness and comfort with the bubble wrap, using it for an extended period may affect the incidence of back pain in evacuees. Finally, we hypothesize that the body pressure dispersion of the bubble wrap may be improved by changing the air-filling rate and the size of the air bubbles.
Keywords: Evacuation shelter; Cardboard bed; Mattress; Back pain; Body pressure distribution; Evacuee; Musculoskeletal burden; Ergonomics; Health care; Disaster victims